Building Holistic Character in Independent Curriculum-Based Education in the Digital Era - Afrianti, Bestaria; Wahab, Wahab (Jurnal Pengabdian Nusantara, 2025)
This article discusses the importance of building holistic character in education through Merdeka Curriculum in the digital era. The author emphasizes that current technological developments and social dynamics require an educational approach that focuses not only on knowledge transfer, but also on comprehensive skill development, including psychological, social, and emotional aspects. Character education is expected to form individuals with integrity and responsibility, and be able to face the challenges of the times. The Merdeka curriculum is designed to develop students' potential by emphasizing Pancasila values and good character. The research method used is a literature review, which shows that holistic education can help students adapt to rapid changes in the digital era. In addition, this article highlights the importance of character education in developing 21st century skills, such as creativity, collaboration and problem-solving. Teachers are expected to adapt to new technologies and learning methods, such as blended learning, to create an effective learning environment. Despite challenges such as online safety and plagiarism, digital learning also offers opportunities to improve the quality of character education. By combining tradition and modern technology, holistic education prepares students to face future challenges with ethical values and relevant skills. The implementation of a developmentally appropriate curriculum is crucial to achieving this goal.